2011
DOI: 10.1007/s12640-011-9243-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Immobilization Stress Increases Nur77 Expression in the Bed Nucleus of the Stria Terminalis

Abstract: The transcription factor Nur77 has been identified as a neuronal activation marker of stressful stimuli in the central nervous system. Nur77 plays a key role at all levels of the hypothalamus-pituitary-adrenal axis during the stress response. However, the participation of Nur77 in extra-hypothalamic responses to stress is unknown. In this study, we studied the impact of acute and repeated immobilization stress on Nur77 expression in the bed nucleus of stria terminalis (BNST), a region involved in autonomic, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
(103 reference statements)
0
8
1
Order By: Relevance
“…In the PVN, it has been shown that Nur77 is no longer induced after chronic stress stimuli (Umemoto et al, 1994, 1997). In contrast, in the ventral region of the BNST, we observed a higher number of cells expressing Nur77 after repeated immobilization stress compared with acute stress (Campos-Melo et al, 2011). Interestingly, the data of the group of Marta Antonelli (Katunar et al, 2010) suggest that Nurr1 may be the transcription factor setting up the new parameters of the dopamine system after prenatal stress.…”
Section: Functional Role Of Nur Transcription Factors In the Addictiocontrasting
confidence: 55%
See 1 more Smart Citation
“…In the PVN, it has been shown that Nur77 is no longer induced after chronic stress stimuli (Umemoto et al, 1994, 1997). In contrast, in the ventral region of the BNST, we observed a higher number of cells expressing Nur77 after repeated immobilization stress compared with acute stress (Campos-Melo et al, 2011). Interestingly, the data of the group of Marta Antonelli (Katunar et al, 2010) suggest that Nurr1 may be the transcription factor setting up the new parameters of the dopamine system after prenatal stress.…”
Section: Functional Role Of Nur Transcription Factors In the Addictiocontrasting
confidence: 55%
“…We reported that cells expressing CRF in the BNST also express Nur77 (Campos-Melo et al, 2011), even though the expression of Nur77 is wider than CRF in this nucleus. Nur77 expression increases significantly in the dorso-lateral and ventro-medial subdivisions of the BNST after acute and repeated immobilization stress (Campos-Melo et al, 2011), same areas where CRF expression increases after repeated immobilization stress (Santibanez et al, 2006). Several years ago, it was shown that the intracerebroventricular injection of CRF increases CRF expression in the PVN (Parkes et al, 1993).…”
Section: Nur Transcription Factors During the Stress Responsementioning
confidence: 93%
“…Immunofluorescence assays were performed essentially as described previously (32). Brain slices were incubated with anti-CoREST1 (612146 from BD Transduction Laboratories) for 48 h at 4°C, and then anti-CoREST2 (HPA021638 from Sigma) was added, followed by incubation for 12 h. Subsequently, slices were mounted on glass slides and incubated with secondary anti-rabbit IgG coupled to Alexa Fluor 594 and anti-mouse IgG coupled to Alexa Fluor 488.…”
Section: Animalsmentioning
confidence: 99%
“…Nr4a1, like other Nr4a members, is involved in early sympathetic stress response in the neuroendocrine system 811 . At the same time, Nr4a1 plays an important role in leukocytes, where it is a central regulator of innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%